A two-sector model of the business cycle: a preliminary analysis - Giancarlo Gozzi; Franco Nardini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2000)
In this paper a two-sector dynamic model of business fluctuations is presented. It is a disequilibrium dynamic model with two laws of evolution (dynamic laws) built into it: prices of commodities change according to the market disequilibrium of supply and demand, while quantities change according to the stock disequilibrium and the shifting of the degree of utilization of productive capacity away from its target value. Investment by firms is modelled by a nonlinear accelerator. Non linearity in the investment function makes the equilibria of the model unstable and causes growing disproportionalities between the two sectors; business fluctuations are the outcome of the switching of the system to a different regime that allows to reduce the existing disproportionality. The different regimes into which the economy may be found are a situation of overheating and one of depression. A fundamental role in the switching of the economy is played by two crucial features of the capital good sector: its limited productive capacity and the time-lag required to increase it.
Keywords: 330